2008
DOI: 10.1038/nm1710
|View full text |Cite
|
Sign up to set email alerts
|

IL-22 mediates mucosal host defense against Gram-negative bacterial pneumonia

Abstract: Emerging evidence supports the concept that T helper type 17 (T H 17) cells, in addition to mediating autoimmunity, have key roles in mucosal immunity against extracellular pathogens. Interleukin-22 (IL-22) and IL-17A are both effector cytokines produced by the T H 17 lineage, and both were crucial for maintaining local control of the Gram-negative pulmonary pathogen, Klebsiella pneumoniae. Although both cytokines regulated CXC chemokines and granulocyte colony-stimulating factor production in the lung, only I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

44
1,129
14
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,045 publications
(1,198 citation statements)
references
References 40 publications
44
1,129
14
11
Order By: Relevance
“…The proinflammatory/pathological nature is apparent in mouse models with diseases such as psoriasis [4] and rheumatoid arthritis [22], and T. gondii infection [11]. In contrast, IL-22 plays protective roles and has tissue-protective and antimicrobial properties in several mouse models with diseases such as inflammatory bowel disease (IBD) [23], hepatitis [24] and infection with invading pathogenic bacteria [10,25,26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proinflammatory/pathological nature is apparent in mouse models with diseases such as psoriasis [4] and rheumatoid arthritis [22], and T. gondii infection [11]. In contrast, IL-22 plays protective roles and has tissue-protective and antimicrobial properties in several mouse models with diseases such as inflammatory bowel disease (IBD) [23], hepatitis [24] and infection with invading pathogenic bacteria [10,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…In infection with an attenuated strain of Salmonella enterica serovar Enteritidis, p19-deficient mice showed reduced survival and exacerbated liver necrosis only in the absence of IL-12 in an IL-17-independent manner [10]. In peroral infection with Toxoplasma gondii, which leads to the development of small intestine inflammation, the IL-23-dependent upregulation of IL-22 is essential for the development of ileitis; on the other hand, IL-17 is downregulated and dispensable [11].IL-22 is a member of the IL-10 cytokine family and plays important roles in inflammation, immune surveillance and tissue homeostasis [12][13][14][15] [10,25,26].Recently, we demonstrated that Notch, which is an evolutionally conserved molecule that controls cell fate decision in a variety of cells [27,28], drives IL-22 secretion by stimulating the AHR [29]. Mice that are deficient in RBP-J, a key mediator of Notch signaling, are highly susceptible to the detrimental immunopathology associated with Con A-induced hepatitis with little IL-22 production [29].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, the inoculation of Lm-infected macrophages into C57BL/6 mice strongly induced the production of IFN-c and IL-22 ( Figure 1c), two potent mediators of cellular inflammatory responses against bacterial pathogens. [19][20][21] In addition, IFN-c-producing CD4 1 T cells were analyzed by FACS and showed to be consistently present ( Figure 1d). This result was not due to the contamination of live Lm escaping from the infected macrophages, since the mice were treated with gentamicin before and after adoptive transfer.…”
Section: Resultsmentioning
confidence: 93%
“…On the one hand, in the context of psoriasis lesions, IL-22 definitely plays a proinflammatory role. On the other hand, IL-22 exerts a protective effect in inflammatory and infectious processes affecting the intestinal and respiratory mucosa, both by inducing the production of anti-microbial proteins and by promoting homeostasis of epithelial cells [43][44][45][46][47]. IL-22 also plays a protective role in an hepatitis model by promoting hepatocyte survival [48,49].…”
Section: Il-22mentioning
confidence: 99%